The content of vitamin C in short-shelf-life (24 hrs) juices available commercially and produced at home - J. Stankiewicz; B. Wieczorkiewicz (Scientific Journal of Gdynia Maritime University, 2017)
The level of vitamin C in apple juices is conditioned by many factors, which include; the variety and origin of apples, processing method and storage conditions at the point of sale. The aim of the study was to compare the content of vitamin C in single-ingredient apple juices that are available at retail outlets and those pressed at home. The study material consisted of not-from-concentrate apple juice samples produced by eight different manufacturers that were either, refrigerated or stored in ambient temperature at the point of purchase. Samples of home-pressed juice differed in terms of apple varieties, retail outlets where the apples were purchased, their country of origin and price. The highest content of vitamin C was noted in commercially available juices whose producers stated an addition of L-ascorbic acid on their packaging. Only two commercially available juices had vitamin C content similar to the amount of this compound found in homemade juices. The level of vitamin C in juices pressed at home depended on the apple variety.